2019
DOI: 10.1038/s41598-018-38064-7
|View full text |Cite
|
Sign up to set email alerts
|

2-aminoimidazoles collapse mycobacterial proton motive force and block the electron transport chain

Abstract: There is an urgent need to develop new drugs against tuberculosis. In particular, it is critical to target drug tolerant Mycobacterium tuberculosis (M. tuberculosis), responsible, in part, for the lengthy antibiotic regimen required for treatment. We previously postulated that the presence of in vivo biofilm-like communities of M. tuberculosis could contribute to this drug tolerance. Consistent with this hypothesis, certain 2-aminoimidazole (2-AIs) molecules with anti-biofilm activity were shown to revert myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 62 publications
3
33
1
Order By: Relevance
“…The main arguments in favor of Mitchell's chemiosmotic theory were based on the ability of uncouplers to cause the collapse of the membrane potential by carrying protons across membranes. At present, there is a revival of interest in uncouplers because of the growing evidence of their broad-spectrum therapeutic efficacy [1][2][3][4][5][6][7][8][9], including antibacterial potency [10][11][12][13][14][15][16][17][18][19], which was actually found very early [20]. To this end, a series of esters of fluorescein were obtained and studied at our laboratory, manifesting themselves as rather effective mitochondrial uncouplers [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The main arguments in favor of Mitchell's chemiosmotic theory were based on the ability of uncouplers to cause the collapse of the membrane potential by carrying protons across membranes. At present, there is a revival of interest in uncouplers because of the growing evidence of their broad-spectrum therapeutic efficacy [1][2][3][4][5][6][7][8][9], including antibacterial potency [10][11][12][13][14][15][16][17][18][19], which was actually found very early [20]. To this end, a series of esters of fluorescein were obtained and studied at our laboratory, manifesting themselves as rather effective mitochondrial uncouplers [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al screened a set of 700 compounds from the CSIR-IIIM repository for inhibition of mycobacterial ATP synthase activity using IMVs of M. smeg, leading to the identification of two compounds, the thiazolidine 5228485 and the cyclohexanediones 5220632. Both compounds inhibited ATP synthesis in IMVs and had MICs in the low micromolar range [184]. These bactericidal compounds were active against drug-resistant M. tb strains and non-replicating M. tb without apparent cytotoxicity [184].…”
Section: Bdqmentioning
confidence: 99%
“…Both compounds inhibited ATP synthesis in IMVs and had MICs in the low micromolar range [184]. These bactericidal compounds were active against drug-resistant M. tb strains and non-replicating M. tb without apparent cytotoxicity [184]. Mutants selected against each compound were cross-resistant to BDQ, although resistance studies additionally suggest that these compounds may inhibit a secondary target besides the ATP synthase [184].…”
Section: Bdqmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] We have previously demonstrated that activity against M. smegmatis often translates to activity against M. tuberculosis. [8,9] Recently, we reported that analogues of the marine natural product meridianin D, 1 (Figure 1), inhibit and disperse biofilms of M. smegmatis. [10] Lead compound 2 was shown to be superior to 1 and demonstrated the ability to inhibit biofilms at low micromolar concentrations as well as the ability to disperse preformed biofilms.…”
Section: Introductionmentioning
confidence: 99%